POST-TRUMP DIPLOMACY OUTLOOK - Figueiredo, Eurico de Lima; Migon, Eduardo Xavier Ferreira Glaser; Visentini, Paulo; Pecequilo, Cristina Soreanu; Martins, José Miguel Quedi; da Silva, Athos Munhoz Moreira; Ianhez, Rodrigo; Thudium, Guilherme; Geiger, Luana Margarete; Ribeiro, Erik Herejk (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The electoral defeat of Republican candidate Donald Trump and the return of the Democrats to the White House cannot be left unexamined, considering its implications for international relations. Here we present introductory notes of NERINT's Strategic Analysis series, written by experts and divided into thematic issues and bilateral relations between the United States and the most relevant nations at the global level.